Magnetic versus crystal-field linear dichroism in NiO thin films - Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2004)
We have detected strong dichroism in the Ni L2,3 x-ray absorption spectra of a monolayer NiO film. The dichroic signal appears to be very similar to the magnetic linear dichroism observed for thicker antiferromagnetic NiO films. Detailed analysis reveals, however, that the dichroism is caused by crystal-field effects in the monolayer film, which is a nontrivial effect because the high spin Ni 3d8 ground state is not split by low-symmetry crystal fields. We present a practical method for identifying the independent magnetic and crystal-field contributions to the linear dichroic signal in spectra of NiO films with arbitrary thicknesses and lattice strains. Our findings are also relevant for 3d5 and 3d3 systems such as LaFeO3, Fe2O3, VO, LaCrO3, Cr2O3, and Mn4+ thin films.